Emotional intelligence and burnout among medical officers of twin cities in Pakistan - Yaqoob, Nazia; Zulfiqar, Somia (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the level of burnout and emotional intelligence among junior and senior medical officers. Methods: The cross-sectional observational study was conducted at the Department of Applied Psychology, Government College Women University, Faisalabad, Pakistan, from February to December 2017, and comprised medical officers of either gender aged 25-45 years with professional experience 1-10 years enrolled from different government and private hospitals of Faisalabad and Lahore. Data was collected using Schutte Emotional intelligence Test and Professional Quality of Life scale. Data wsa analysed using SPSS 21. Results: Of the 160 subjects, 90(%) were male and 70(%) were female medical officers. The overall mean age was 29.39±4.65 years, Further, 95(59.4%) subjects had professional experience 1-2 years, while 65(40.6%) had 3-10 years. Junior medical officers experienced significantly higher level of burnout and emotional intelligence compared to the seniors (p<0.05). Conclusion: Junior medical officers were found to have significantly higher level of burnout and emotional intelligence compared to the seniors. Key Words: Burnout, Medical officers, Emotional intelligence, T-test.